PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING BERBANTUAN MEDIA VIDEO FUNMATH TERHADAP KEMAMPUAN PEMAHAMAN KONSEP SISWA KELAS III - Ardila, Luthfi Reza; Lisa Virdinarti Putra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of guided inquiry learning model assisted by FunMath video media on the ability to understand mathematical concepts of third grade elementary school students. The study used a quantitative approach with a quasi-experimental design of the Nonequivalent Control Group Design type. The research sample consisted of two classes, namely class IIIA as the experimental class and class IIIB as the control class, each with 20 samples. The instrument was a mathematical concept understanding test that had met the validity and reliability criteria with a Cronbach's alpha value of 0.777. The results showed that the average pretest-posttest score in the experimental class increased from 46.00 ± 6.92 to 83.10 ± 6.55, while in the control class it increased from 48.10 ± 7.01 to 74.40 ± 7.12. The Paired Sample T-test showed a significant difference between the pretest and posttest in the experimental class (t = −22.995; p < 0.001). An independent sample t-test showed a significant difference between the experimental and control classes in the posttest (p < 0.05). The treatment effect was in the medium-strong category with an effect size (Cohen's d) of 1.63. These results indicate that the guided inquiry learning model assisted by FunMath video media effectively improves the mathematical concept understanding ability of third-grade elementary school students.